Trade analysis among ASEAN, Japan, Korea and China / Chew Shiau Ping - Chew , Shiau Ping (2021)
This study explores the central problem of whether the regional economic co-operation – ASEAN plus Three (APT) - can produce beneficial trade creation or harmful trade diversion effects on ASEAN’s export industries with the objectives: (1) to examine the trade relationship among APT; (2) to explain the factors affecting changes in the pattern of trade among them; (3) to explore the qualitative issues of whether the presence of high technology exports signifies technological capability in the context of ASEAN; and (4) to explore the implications of ASEAN’s role in these supply chains, and how dependent are they on China in terms of inputs or outputs. It found that the rise of China as ASEAN’s most important trading partner, displacing mainly Japan, while South Korea is not a big trading partner, is especially significant. Then, the indices such as revealed comparative advantage, trade complementarity and intra-industry trade, all point to trade creation as a consequence of APT. However, ASEAN lacks domestic technological capability related to domestic constrains and needs to develop capability domestically. Furthermore, there is evidence of China’s growing importance in the many supply chains ending there. The implications for ASEAN countries lagging increasingly behind China are ominous. Overall, the results of this study point to the need for ASEAN member states as a whole to upgrade their technological capability through training programs or emulate Singapore’s Technical and Vocational Education and Training (TVET) system.